Fear of being laughed at with relation to parent attachment in individuals with autism. (February 2015) - Wu, Ching-Lin; An, Chih-Pei; Tseng, Lei-Pin; Chen, Hsueh-Chih; Chan, Yu-Chen; Cho, Shu-Ling; Tsai, Meng-Ling
Highlights: We investigate the relationship between fear of being laughed at (gelotophobia) and parent attachment in individuals with autism. The tendency towards gelotophobia had a notably negative correlation with paternal attachment in the autism group. Individuals with autism have a higher tendency towards gelotophobia and dislike being laughed at among Asian sample. The tendency towards gelotophobia is different across cultures. Abstract: The model of putative causes and consequences of gelotophobia (i.e., the fear of being laughed at) assumes that the fear of being laughed at develops as a consequence of (1) individuals' having been laughed at over a long period of time and (2) failing interactions with parents. Past studies show that individuals with autism are subjected to being laughed at and that they tend to worry about being laughed at or ridiculed, but empirical studies investigating the interactions of individuals with autism with parents and these connections between these interactions and gelotophobia have been lacking. The purpose of this study was to identify the characteristics of gelotophobia in individuals with autism and to determine how these characteristics are connected to parental attachment. This study was conducted on 101 students of average intelligence with autism and 163 without autism, with homogeneous ages and gender ratios between the groups. The methods of research consisted of the PhoPhiKat-TC questionnaire and the Inventory of Parent and Peer Attachment (IPPA). Compared to students without autism, students with autism were found to exhibit a higher level of fear and dislike of being laughed at but showed no difference from students without autism in enjoying laughing at others. In addition, gelotophobia in students with autism was related to attachment to the student's father but not attachment to the mother, thereby implicating a role for paternal interactions in its development. To decrease the tendency that adolescents with autism have towards exhibiting gelotophobia, this study suggests improving child–father interactions through parent education.